Modeling the impact of nature-based solutions on dry season water availability: exploration of spatio-temporal configurations - Garima Mandavya; Sadie McEvoy; Tolulope Odunola; Umit Taner; Xi Chen; Drew McAvoy; Koen Verbist; Patrick Ray (Journal of Hydrology, 2026)

Shifting Patterns in the Weather Regimes That Drive Regional Drought: Demonstration for South Africa - Garima Mandavya; Gaurav Atreya; John Kucharski; Andrew Watson; Nasser Najibi; Koen Verbist; Patrick Ray (International Journal of Climatology, 2025)
Traditional vulnerability assessments of climate change impacts often rely on randomised precipitation scenarios that lack a strong physical science basis. Furthermore, the limitations of General Circulation Models (GCMs) in accurately representing local precipitation fields undermine their utility for projecting future hydroclimatic extremes. To address these gaps in climate risk management, this study explores the role of large‐scale atmospheric circulation patterns, known as weather regimes (WRs), in explaining local and regional precipitation dynamics in South Africa. Utilising a Non‐Homogeneous Hidden Markov Chain approach, we identified six primary WRs for South Africa, each exhibiting distinct seasonal patterns. The results show that winter precipitation near Cape Town is dominated by three WRs linked to higher rainfall, whilst summer precipitation is influenced by two WRs associated with drier conditions. The WR‐precipitation relationship in South Africa appears to be influenced by topographic features (e.g., The Great Escarpment and Cape Fold Mountains) and ocean currents (Agulhas and Benguela), leading to distinct spatial precipitation responses to regional WR configurations. Importantly, significant shifts in seasonal WR frequencies have been observed over the past two decades, particularly a marked change since 2010. Notably, a WR historically associated with rainfall in Cape Town has been replaced by a drier WR, contributing to worsening drought conditions, including the 2015–2017 “Day Zero” drought. During this period, the WR associated with dryness in Cape Town occurred more frequently than the historical average, whilst wetter years before and after the drought were characterised by low‐pressure (low 500 hPa geopotential height anomalies) WRs conducive to precipitation. In contrast, the drought years were dominated by high‐pressure (high 500 hPa geopotential height anomaly) WRs associated with dry conditions. This WR‐precipitation analysis underscores the critical link between atmospheric circulation patterns and regional hydroclimatic extremes. These findings can inform the development of WR‐based rainfall generators, providing valuable tools for vulnerability assessments and climate change adaptation planning.

Remote sensing-enabled machine learning for river water quality modeling under multidimensional uncertainty - Saiful Haque Rahat; Todd Steissberg; Won Chang; Xi Chen; Garima Mandavya; Jacob Tracy; Asphota Wasti; Gaurav Atreya; Shah Saki; Md Abul Ehsan Bhuiyan; Patrick Ray (Science of The Total Environment, 2023)